Endothelial keratoplasty with anterior chamber intraocular lens versus secondary posterior chamber intraocular lens. Issue 2 (28th October 2020) - Woo, Jyh Haur; Arundhati, Anshu; Chee, Soon-Phaik; Tong, Weihan; Li, Lim; Ti, Seng-Ei; Htoon, Hla M; Choo, Jessica Qian Hui; Tan, Donald; Mehta, Jodhbir S
Abstract : Aim: To describe the long-term outcomes of Descemet stripping automated endothelial keratoplasty (DSAEK) with an anterior chamber intraocular lens (ACIOL) compared to secondary posterior chamber (PC) IOL. Methods: This was a retrospective comparative cohort study. The clinical data of 82 eyes from 82 consecutive patients with pseudophakic (PBK) or aphakic bullous keratopathy (ABK) who either underwent DSAEK with retained or secondary ACIOL (n=23) or DSAEK with IOL exchange and/or secondary PCIOL (retropupillary iris-claw IOL, n=25; intrascleral-fixated IOL, n=29; or sulcus IOL, n=5) were analysed. The main outcome measures were graft survival and complications up to 5 years. Results: The graft survival in the secondary PCIOL group was superior than the ACIOL group over 5 years (year 1, 100.0% vs 100.0%; year 3, 94.7% vs 75.0%; year 5, 91.1% vs 60.6%, p=0.022). The presence of an ACIOL was a significant risk factor associated with graft failure (HR, 4.801; 95% CI, 1.406 to 16.396, p=0.012) compared to a secondary PCIOL. There was no significant difference in the rate of graft detachment and elevated intraocular pressure between the groups. There were five cases (9.3%) of IOL subluxation or dislocation in the retropupillary iris-claw and intrascleral-fixated IOL groups. Conclusions: Eyes that underwent DSAEK with ACIOL in situ had poorer long-term graft survival compared with those with secondary PCIOL. Intraocular lens exchange was not associated with a higher complication rate. In ABK or PBK eyes with ACIOL, we recommend performing IOL exchange and/or secondary PCIOL implantation combined with endothelial keratoplasty.